Artificial Intelligence (AI)-based Learning Media: Definition, Bibliometric, Classification, and Issues for Enhancing Creative Thinking in Education - Solihat, Ai Nur; Dahlan, Dadang; Kusnendi, K.; Susetyo, Budi; Al Obaidi, Abdulkareem Sh. Mahdi (ASEAN Journal of Science and Engineering, 2024)
This research aims to identify effective ways of integrating Artificial Intelligence (AI) technology with innovative learning methods to improve students' creative thinking skills in various educational contexts. The bibliometric method, a quantitative and statistical approach to bibliographic data such as publications and citations, serves as the research method. Data were collected on July 2024, through the SCOPUS database using the keywords "creative thinking" OR "creative thinking skills" AND "creativity.". Data analysis was conducted in three stages: data collection, visualization, and analysis using software such as VosViewer. The results showed research trends, knowledge gaps, and potential new research areas relevant to technology integration in education. This research contributes to developing more effective and inclusive education policies and practices by ensuring all students have equal opportunities to develop essential skills in the digital age. Limitations of this study include limited access to technology in some areas and a need for teacher training in integrating AI into the learning process. Future research recommendations include focusing more on improving access to technology and teacher training to effectively use AI technology in education.